Enablers of Target Cost Management Implementation: Evidence from Malaysia - Baharudin, Norhafiza; Jusoh, Ruzita (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study used contingency theory to examine the key enablers of target cost management (TCM) at the Malaysian context. Using a single case study approach, a questionnaire survey was conducted on users of TCM at Company A, a Malaysian automotive company. The respondents were required to determine whether enablers, namely, an advanced manufacturing technology (AMT) implementation, confrontational strategy, customer orientation, an information-sharing network, lean manufacturing implementation, supplier relationships, teamwork oriented organizational culture, top management support and commitment, and training havepositive relationships with the successful implementation of TCM. The findings show that only teamwork, top management support and commitment, and training are the key enablers for the successful implementation of TCM in the case company.